Regenerative Therapy of Type 1 Diabetes Mellitus: From Pancreatic Islet Transplantation to Mesenchymal Stem Cells - Nadine E. Rekittke; Meidjie Ang; Divya Rawat; Rahul Khatri; Thomas Linn (Stem Cells International)
Type 1 diabetes is an autoimmune disease resulting in the permanent destruction of pancreatic islets. Islet transplantation to portal vein provides an approach to compensate for loss of insulin producing cells. Clinical trials demonstrated that even partial islet graft function reduces severe hypoglycemic events in patients. However, therapeutic impact is restrained due to shortage of pancreas organ donors and instant inflammation occurring in the hepatic environment of the graft. We summarize on what is known about regenerative therapy in type 1 diabetes focusing on pancreatic islet transplantation and new avenues of cell substitution. Metabolic pathways and energy production of transplanted cells are required to be balanced and protection from inflammation in their intravascular bed is desired. Mesenchymal stem cells (MSCs) have anti-inflammatory features, and so they are interesting as a therapy for type 1 diabetes. Recently, they were reported to reduce hyperglycemia in diabetic rodents, and they were even discussed as being turned into endodermal or pancreatic progenitor cells. MSCs are recognized to meet the demand of an individual therapy not raising the concerns of embryonic or induced pluripotent stem cells for therapy.